The Evolution of News Production: A Case Study of Pikiran Rakyat Media Network in the Digital Age - Rahman, Fathan Tibyan; Firmansyah, Firmansyah (Hanifiya: Jurnal Studi Agama-Agama, 2025)
Newspaper has become rarely used, and now digital media has emerged as a device that, in addition to being widespread, is also easily accessible. In the contemporary digital era, the dynamics of news communication have undergone a significant transformation, impacting both traditional news outlets and emerging online platforms. This thesis explores the complexities of the transformation of print news communication into digital, with a specific focus on the case of Pikiran Rakyat, a leading news outlet in Indonesia. The digital era has revolutionized the way news is produced, disseminated, and consumed, raising critical questions about how news organizations adapt to this ever-evolving landscape while maintaining their credibility and relevance. Using a comprehensive qualitative research approach, this study delves into the strategies, challenges, and news communication practices at Pikiran Rakyat Media Network (PRMN). The research also investigates how Pikiran Rakyat Media Network responds to the rapidly changing information ecosystem, addresses the challenges posed by misinformation, and sustains its position as a trusted source of news for its readers. To achieve this, the chosen case study methods include observation and interviews. The findings reveal that Pikiran Rakyat Media Network has successfully transformed its management by adopting the Platform Economy model, which facilitates collaboration with local media and accelerates digital news distribution. The transformation involves a gradual process of convergence between print and digital formats, addressing differences in work ethos, audience needs, and medium characteristics to create a more efficient working ecosystem.